I just need help >.<

I cant solve this I just need someone to help me.

I just need help >.<

I cant solve this I just need someone to help me.

Tutors, sign in to answer this question.

The easiest way to find the inverse of a function in my opinion is to first change the f(x) back into y and swap your x's and y's. Doing these things gives you:

x = 6y + 11. After you do this simply solve for y and your answer will be the inverse.

start by substracting 11 on both sides of the equation then divide both sides by 6. this should give you y = (x-11)/6

Grigori S. | Certified Physics and Math Teacher G.S.Certified Physics and Math Teacher G.S.

Inverse fucntions are symmetric with respect to line y=x. Mathematically it can be written as

f(g) = x

where g(x) is the inverse to f(x) (g = f^{-1}). But

f(g) = 6g +11 and thus 6g + 11 = x. Hence it follows g(x) = (x-11)/6

ƒ(x) = 6x + 11

y = 6x + 11 , let's solve this equation for "x"

6x = y - 11

x = (1/6) y - 11/6

Now, switch the "x" and "y"

y = (1/6) x - 11/6

In function notation:

** ƒ ^{ - 1}(x) = (1/6) x – 11/6 **

Already have an account? Log in

By signing up, I agree to Wyzant’s terms of use and privacy policy.

Or

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Your Facebook email address is associated with a Wyzant tutor account. Please use a different email address to create a new student account.

Good news! It looks like you already have an account registered with the email address **you provided**.

It looks like this is your first time here. Welcome!

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Please try again, our system had a problem processing your request.

Alain F.

Native speaker for French and Master in Science Grad for Math!

$13.75 per 15 min

View Profile >

Lisa V.

Patient and Understanding Math, Reading and Test Preparation Tutor

$12 per 15 min

View Profile >

Mary R.

Expertise and Motivation for Success

$10 per 15 min

View Profile >

## Comments

Agreed Xavier. Except at the very end, you should use f

^{-1}(x) = ... instead of y = ... and of course in slope intercept form you have, f-1(x) = (1/6)x - (11/6)kim

Correct. I typed the solution right before I began a session with a student so I had to speed things up a little therefore I didn't display the best use of notation.